Pengaruh Pengendalian Internal, Lingkungan Kerja, Dan Audit Operasional Terhadap Kinerja Pegawai Pada Kementerian Lingkungan Hidup Dan Kehutanan - Albert Juan Osmon Sitorus; Rudy . (Jurnal Ekonomika Dan Bisnis (JEBS), 2026)
The phenomena that occur in the world of work today are quite diverse according to Soedarsa (2014) The first phenomenon, the high rate of employee turnover, the second phenomenon, there are still many companies or offices that pay less attention to human resources, the third phenomenon, the mismatch between education and employee placement is also still a problem. This study aims to determine the Effect of Internal Control, Work Environment and Operational Audit on Employee Performance (Empirical Study at the Ministry of Environment and Forestry of the Republic of Indonesia). This kind of study employs quantitative techniques. Employees of the Ministry of Environment and Forestry make up the study's population. This study used simple random sampling, which is a method of selecting participants from the population at random without taking into account the population's strata. Seventy respondents made up the study's sample. The author disseminated the survey directly to respondents as part of the data gathering strategy. Descriptive statistical tests, data quality tests, multiple linear regression tests, classical assumption tests, and hypothesis testing are all used in this study's data analysis methodology. Internal control, the work environment, and operational audit all had a simultaneous impact on employee performance, according to the findings of the SPSS version 26 test administered after the study was completed. Employee performance was slightly impacted by the internal control variable, whereas operational audit had an impact and the work environment variable had no discernible influence.